The Effectiveness of Psychoeducation Based on Problem-Based Learning to Enhance Subjective Well-Being - Kadek Fitriyanti; Nono Hery Yoenanto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
The 2023 Work Gratitude Day survey shows that 48.9% of employees feel grateful when they get rewards in the form of materials, 41% feel grateful when they get additional leave, and the rest feel grateful for personalized rewards (Lomas, 2024). In fact, individuals feel grateful and happy when they are associated with material things that are general and temporary. Individual happiness and gratitude can be explained through the construction of subjective well-being. Subjective well-being is the ability of individuals to conduct cognitive and affective evaluations of their lives (Diener, 1984). This research aims to provide education and promotive efforts that can be an individual's capital to improve subjective well-being in themselves. The expected output is an increase in knowledge in the form of being able to find creative ways to foster subjective well-being in oneself. The intervention was in the form of psychoeducation which was attended by 24 experimental groups and had the last education at the strata 1 level. Webinars are designed based on problem-based learning. The research design is a quasi-experimental one group pretest and posttest design. Convenience sampling techniques, and hypothesis tests using the Wilcoxon signed-rank statistical test. The results of the analysis test showed that the significance value of p=0.018